A Genetically Informed Longitudinal Study of Loneliness and Dementia Risk in Older Adults - Kim, Alice J.; Gold, Alaina I.; Fenton, Laura; Pilgrim, Matthew J. D.; Lynch, Morgan; Climer, Cailin R.; Penichet, Eric N.; Kam, Alyssa; Beam, Christopher R. (Frontiers in Genetics, 2021)
Although several studies have shown small longitudinal associations between baseline loneliness and subsequent dementia risk, studies rarely test whether change in loneliness predicts dementia risk. Furthermore, as both increase with advancing age, genetic and environmental selection processes may confound the putative causal association between loneliness and dementia risk. We used a sample of 2,476 individual twins from three longitudinal twin studies of aging in the Swedish Twin Registry to test the hypothesis that greater positive change in loneliness predicts greater dementia risk. We then used a sample of 1,632 pairs of twins to evaluate the hypothesis that effects of change in loneliness on dementia risk would remain after adjusting for effects of genetic and environmental variance. Phenotypic model results suggest that mild levels of baseline loneliness predict greater dementia risk. Contrary to our hypothesis, no change in loneliness correlated with dementia risk, regardless of whether genetic and environmental selection confounds were taken into account. Worsening loneliness with age may not confer greater dementia risk.